A MATHEMATICAL MODEL FOR PREDICTING THE PERFORMANCE OF THE RENEWABLE RIVER CURRENT TURBINE WITH CONSIDERATION OF ROTATION - Aditya Rachman (Jurusan Teknik Mesin, Universitas Halu Oleo, 2011)
River current turbine is one of decentralized alternative energy technologies which is believed to have less environmental impacts and to offer no complex civil work. This study is the continuous work of previous study on developing a mathematical model for predicting the performance of river current turbine. In present model, the effect of turbine rotation is included, providing a widening understanding on the behavior of the turbine. To develop the model, the momentum theory which is generally applied for wind turbine is adopted. The result of the model requires inputting parameters of the water velocity, the turbine radius, the wind rotational velocity and the blade rotational velocity to calculate the performance. Verification and parametric study using the model are demonstrated and the limitation of the model is discussed.